2020
DOI: 10.7759/cureus.11401
|View full text |Cite
|
Sign up to set email alerts
|

Second Dose of Epinephrine for Anaphylaxis in the First Aid Setting: A Scoping Review

Abstract: Anaphylaxis is a life-threatening hypersensitivity reaction where rapid, early administration of epinephrine (adrenaline) can be lifesaving in the first aid setting. There are instances where a single dose of epinephrine does not relieve symptoms and a second dose may be required to further mitigate symptoms and preserve life. We performed a scoping review as part of an update to a previously conducted International Liaison Committee on Resuscitation First Aid Task Force (ILCOR) review. PubMed and E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…66À74 This CoSTR was the subject of a scoping review in 2020. 4,5,75 Two studies identified were included; both studies found that for persons requiring treatment with adrenaline for anaphylaxis, two or more doses were required in 8% of 582 patients, and in 28% of 18 patients, respectively. 75 These studies reaffirm the 2015 treatment recommendation for use of a second dose of adrenaline in people with anaphylaxis who fail to improve within 5 À15 min after an initial dose.…”
Section: Anaphylaxismentioning
confidence: 99%
“…66À74 This CoSTR was the subject of a scoping review in 2020. 4,5,75 Two studies identified were included; both studies found that for persons requiring treatment with adrenaline for anaphylaxis, two or more doses were required in 8% of 582 patients, and in 28% of 18 patients, respectively. 75 These studies reaffirm the 2015 treatment recommendation for use of a second dose of adrenaline in people with anaphylaxis who fail to improve within 5 À15 min after an initial dose.…”
Section: Anaphylaxismentioning
confidence: 99%